Effect of utilizing unground and ground normal and black rice husk ash on the mechanical and durability properties of high-strength concrete - Bahri, Syamsul; Mahmud, Hilmi; Shafigh, Payam (Springer, 2018)
The aim of the present study is to investigate the effects of utilizing different processings of normal rice husk ash (RHA) and black rice husk ash (BRHA) on the mechanical and durability properties of high-strength concrete (HSC). Mechanical and durability properties of HSC were evaluated on concrete mixes containing unground BRHA and RHA and ground BRHA and RHA, their average particles sizes being 165, 85, 67 and 24 µm, respectively. The replacement of ordinary Portland cement with the ashes was adopted at 20%. The results showed that incorporating any form of RHA and BRHA in HSC reduced the slump value. The surface areas of RHA and BRHA, not their carbon content, determined the dosage of superplasticizer needed to achieve a targeted slump value. Concrete with unground and ground RHA incorporated exhibited 30% higher compressive strength while unground BRHA produced 30% lower compressive strength than that of the control concrete. Incorporating unground and ground RHA showed a synergy between filler and pozzolanic effect and had insignificant difference in mechanical and durability properties of the concretes. Meanwhile, incorporating ground BRHA showed a dominant filler effect in the concrete. Overall, the improvement of splitting tensile strength and modulus of elasticity of both RHA and GBRHA concrete showed a similar trend to that of the compressive strength of RHA concrete. The durability of concretes with unground and ground RHA and ground BRHA incorporated showed better performance than that of the control concrete. The material with 20% ground BRHA as partial cement replacement in HSC of Grade 50 could be used without any reduction in the mechanical and durability properties. Use of unground BRHA is not recommended because it did not improve these properties.